2001
DOI: 10.1074/jbc.m107532200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Three Types of the Inositol 1,4,5-Trisphosphate Receptor/Ca2+ Channel in the Secretory Granules and Coupling with the Ca2+ Storage Proteins Chromogranins A and B

Abstract: Although the role of secretory granules as the inositol 1,4,5-trisphosphate (IP 3 )-sensitive intracellular Ca 2؉ store and the presence of the IP 3 receptor (IP 3 R)/Ca 2؉ channel on the secretory granule membrane have been established, the identity of the IP 3 R types present in the secretory granules is not known. We have therefore investigated the presence of different types of IP 3 R in the secretory granules of bovine adrenal medullary chromaffin cells using immunogold electron microscopy and found the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 57 publications
7
60
0
Order By: Relevance
“…The foregoing results raised the possibility that the ER and secretory granules were immunoreactive to putative anti-InsP 3 R2 Abs, as shown in bovine AM cells [9]. However, this complexity might be ascribed to heterogeneous immunoreactivities of the Abs used.…”
Section: Immunoblotmentioning
confidence: 95%
See 3 more Smart Citations
“…The foregoing results raised the possibility that the ER and secretory granules were immunoreactive to putative anti-InsP 3 R2 Abs, as shown in bovine AM cells [9]. However, this complexity might be ascribed to heterogeneous immunoreactivities of the Abs used.…”
Section: Immunoblotmentioning
confidence: 95%
“…Furthermore, the nucleoplasm was also shown to have InsP 3 R-like products, as was noted with the Sigma anti-InsP 3 R2 Ab. Thus according to a series of papers by Yoo and his colleagues [9,37], InsP 3 Rs turn out to be present almost everywhere in bovine chromaffin cells. This apparent complexity of InsP 3 R distributions, in our opinion, may at least in part be due to nonspecific binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of InsP 3 R in secretory granules has been a highly conflicting point over the [49] reported that inositol 1,4,5-trisphosphate (InsP 3 ) released Ca 2+ from chromaffin cells secretory vesicles. Immunocytochemical localization of all three types of InsP 3 R in serially sectioned bovine chromaffin cells showed that the secretory granules contained about 60% of the InsP 3 R in the cell [50], and additional evidence for the presence of InsP 3 R in the granules was the finding that both chromogranin A and B interact with InsP 3 R and modulate its activity [26,[51][52][53][54]. More recently, using targeted aequorin to measure [Ca 2+ ] in the secretory granules of chromaffin cells and the neurosecretory cell lines PC12 and INS1 [23,24], we have shown that InsP 3 and InsP 3 -releasing agonists can release Ca 2+ from the granular compartment (see Fig.…”
Section: Mechanisms Of Ca 2+ Release From the Secretory Granulesmentioning
confidence: 99%